Manajemen Pendidikan dalam Era Reformasi - Willem Mantja (Universitas Negeri Malang, 2016)
Planning, Organizing, actuating, and controlling are the functions of educational management of all kinds of fields of management. The differences between educational management and others are in the components of its substances. Educational management components include instructional, personnel, student, facilitation, financial, include and school public relation management. The educational managers in the reform era require a competence and managerial skills to perform their jobs as professional managers